MENINGKATKAN PEMAHAMAN SISWA PADA MATERI PEDULI LINGKUNGAN MENGGUNAKAN METODE DEMONSTRASI DI KELAS IV DI SDN 12 BULUH ENGGADANG - wiwin januarti; Muhammad Sobri (LP2M IAI NURUL HAKIM, 2023)
Improving the Understanding of Students who Care for the Environment with the Class IV Demonstration Method at SDN 12 Buluh Enggadang is the title of Consolidating Professional Capabilities written by Wiwin Januarti. The problem in this learning is that students do not understand the material from Caring for the Environment. As a result, the teacher wants to achieve the learning objectives, namely to find out why students do not understand the material from Care for the Environment and make science lessons more creative and innovative for teachers. The instrument in this study used the observation method in which there were test questions and attitude tests. The sample is grade IV students, totaling 21 children. So that it can be analyzed that the demonstration model can add to students' understanding in understanding science lessons for fourth grade students at SDN 12 Buluh Enggadang for the 2022/2023 academic year, it can be seen from students 1) Have found examples of concern for the environment for themselves when working on LKS questions after being demonstrated 2 ) The demonstration method increases the average value of the average daily exercise score for cycle 1, which is 73.80 with a completeness percentage of 57.14% and the average for cycle II is 86.9 with a passing percentage of 90.47. With the results of this study, as a teacher can guide learning with a variety of methods that are appropriate and when understanding environmental material, the demonstration method is one of them in a teacher's teaching activities.